Collection of ferns in the historical herbarium of Uman College of Agriculture and Horticulture - Чорна, Г. А.; Куземко, А. А.; Діденко, І. П. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The results of the study of ferns collection of the historical herbarium of Uman College of Agriculture and Horticulture (end of XIX – beginning of XX century), stored in the scientific herbarium of the National Dendrological Park "Sofiyivka" of NAS of Ukraine have been presented. The basic biographical data about collectors have been given, geography and habitat characteristics of the samples have been analyzed, and the results of the taxonomic treatment of 42 herbarium specimens of the collection, in accordance with their current nomenclature – 28 species, 19 genera, 11 families, 2 division have been presented. Studied herbarium samples are ecsiccatae of «Herbarium Florae Rossicae». These ecsiccatae are represented by collections made by famous botanists, in particular D.I.Litvinov (one of founders of this edition), V.I.Lipsky, M.I.Zinger, Yu.M.Voronov etc. in Finland, Vilna Governorate (Lithuania), Eastern Manchuria, Primorye of Far East of Russia.